PENGEMBANGAN BAHAN AJAR BERBASIS MAJALAH SISWA PINTAR FISIKA (MSPF) UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Maryati, Ita Fitri; Gummah, Syifaul; Sukroyanti, Baiq Azmi (Jurnal Ilmiah IKIP Mataram, 2018)
This research has developed teaching materials based on Smart Magazine Physics (SMP) to improve student learning outcomes. The research method uses Research and Development (R & D) through three stages of the 4-D model as follows: Define, Design, and Develop. Instruments used are validation sheet of experts and test-trial. The results show that the average score of experts for Smart Magazine Physics (SMP) is 3,71 (category ‘very valid’). Meanwhile, the average score for the trial of 32 students is 3,2 (good category). It can be concluded that Smart Magazine Physics (SMP) has been developedis recommended to improve student learning outcomes.